The marketing strategy of the business complex-case study of Xi Ying Men - Wu, Jin; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
In recent years, due to the government's increased supervision on the real estate industry, the growth rate of the commercial real estate market has slowed down, and it is difficult to de inventory in some regions, and the structural contradiction has become increasingly prominent. With the rise and development of e-commerce, traditional integrated commercial entities are facing a severe development situation. Xiyingmen Building Materials and Home Furnishings Plaza was founded in 1997 and headquartered in Shanghai. It specializes in the development, operation and management of urban complex and building materials and furniture plaza projects. Because of its early start and perfect supporting facilities, it also achieved good financial performance in the early stage. However, with the continuous emergence of large commercial complexes, the pattern of new and old business districts has changed significantly, and the competition between commercial complexes has become increasingly fierce. The financial performance of Xiyingmen Building Materials and Home Furnishing Plaza has declined year by year. Therefore, it is urgent to carry out special research, propose feasible measures, summarize effective experience, which is conducive to promoting the sustainable development of the industry, bringing better benefits to the operation of the industry, and can provide theoretical reference for the formulation of marketing strategies for many similar commercial complexes. From the perspective of the demand and service of target merchants and consumers, this paper first analyzes the macro environment analysis, regional business development analysis, competitor comparison analysis, project positioning analysis, SWOT analysis and other aspects of Xiyingmen Building Materials and Home Furnishing Plaza, which provides a solid foundation and reference value for the project to formulate marketing strategies.